An effective and potentially safe blood disinfection protocol using tetrapyrrolic photosensitizers. (March 2017) - Marciel, Lúcia; Teles, Luís; Moreira, Beatriz; Pacheco, Mário; Lourenço, Leandro MO; Neves, Maria GPMS; Tomé, João PC; Faustino, Maria AF; Almeida, Adelaide
Aim: Conventional disinfection techniques, considered safe for plasma, are usually associated with collateral damages on concentrated platelets and erythrocytes. Alternative methods are required and antimicrobial photodynamic therapy (aPDT) seems promising. In this study the effectiveness of two photosensitizers (PS), a porphyrin and a phthalocyanine, to disinfect blood products was evaluated.Results: The cationic porphyrin was more effective in the photoinactivation of bacteria. Also, no significant osmotic stress was found for samples treated with PS at 5.0 µM in isotonic conditions after antimicrobial photodynamic therapy.Conclusion: Effective reduction of Gram-positive bacteria at 5.0 µM of PS provided promising indications toward its safe use to disinfect blood samples. For Gram-negative bacteria, lower PS concentrations, between 5.0 and 10 µM, must be tested.